Europe at the seaside : the economic history of mass tourism in the Mediterranean - Segreto, Luciano; Manera, Carles, 1957-; Pohl, Manfred, 1944- (Berghahn Books, 2009)
Mass tourism is one of the most striking developments in postwar western societies, involving economic, social, cultural, and anthropological factors. For many countries it has become a significant, if not the primary, source of income for the resident population. The Mediterranean basin, which has long been a very popular destination, is explored here in the first study to scrutinize the region as a whole and over a long period of time. In particular, it investigates the area's economic and social networks directly involved in tourism, which includes examining the most popular spots that attr.